Histological and histochemical studies on the oviduct of sheep during follicular and luteal phases of the estrous cycle - Pathak, Devendra; Nagpal, S K; Singh, Gurdial (Indian Journal of Veterinary Anatomy, 2023)
The present study explored the histology and histochemistry of the oviduct of sheep in the follicular and luteal phases of estrous cycle. Histological studies of the oviduct of sheep revealed extensive primary and secondary branching of the mucosa! folds in the infundibulum and ampulla which reduced towards the isthmus and utero tubal junction. The epithelial lining of different segments of the oviduct was mainly pseudostratified columnar type. Cells were of the ciliated type, secretory type, basal cells and migratory cells. Cyclic changes in the tubal epithelium were more pronounced in the upper part of the oviduct than in the isthmus and utero-tubal junction. The propria submucosa was made up ofloose connective tissue comprising collagen and reticulum. The cellular components of propria submucosa comprised fibroblasts, lymphocytes and macrophages. The tunica muscularis was circularly arranged. Tunica serosa was comprised of loose connective tissue. It was vascular and moderately cellular. The epithelium of the oviduct showed a strong reaction for PAS, Alcian Blue (at pH 2.5) and PAS-Alcian Blue (pH 2.5).It exhibited moderate reaction for bound acidic and neutral lipids. RNA was localized in the apical region while DNA was localized towards the basement membrane. Propria submucosa was weak for polysaccharides, glycogen and lipids. Tunica muscularis and tunica serosa were weak to moderately reactive for carbohydrates and lipids. RNA and DNA were localized homogeneously.